Creating Video Processing Suite Using Java Media Framework - Logenthiran A/L Manogaran, Logenthiran (2009)
This project is to develop a video processing suite using Java Media Framework. Previously an advanced video processing suite has been successfully been developed in MATLAB. However, due to the expensive licensing fees of MATLAB, not all computers are able to be equipped with it and this has limited a wider usage of the suite.